Applications of daunorubicin-loaded PLGA-PLL-PEG-Tf nanoparticles in hematologic malignancies: an in vitro and in vivo evaluation - Bao W; Liu R; Xia G; Wang F; Chen B (Dove Medical Press, 2019)
Wen Bao, Ran Liu, Guohua Xia, Fei Wang, Baoan Chen Department of Hematology and Oncology, Key Medical Disciplines of Jiangsu Province, Zhongda Hospital, Medical School of Southeast University, Nanjing 210009, People’s Republic of China Background: With the development of drug delivery, novel tools and technological approaches have captured the attention of researchers in recent years. Several target drug delivery systems (DDSs) including nanoparticles (NPs) have been developed as an important strategy to deliver classical medicine. Objective: The objective of this study was to evaluate the application of novel daunorubicin (DNR)-loaded poly(lactic-co-glycolic acid)-poly-l-lysine-polyethylene glycol-transferrin (Tf) nanoparticles (DNR-loaded NPs) in hematologic malignancies in vitro and in vivo. Materials and methods: DNR-loaded NPs were prepared by the modified double-emulsion solvent evaporation/diffusion method, and its microscopic form was observed under scanning electron microscope. Intracellular distribution of DNR was directly detected by fluorescence microscopy. After establishment of a tumor xenograft model by injecting K562 cells into the left leg of nude mice, the therapeutic effect of the DNR-loaded NPs on the growth of tumors was measured by calculating the tumor size, and the relative expression of Caspase-3 protein was detected by immunohistochemical staining. Furthermore, intracellular concentration of DNR and the extent of cell apoptosis in primary leukemia cells were quantified by flow cytometry. Results: DNR-loaded NPs had a spherical shape of about 180 nm in diameter. DNR-loaded NP group showed a significant enhancement of cellular uptake in K562 cells compared with DNR group. Tumor inhibition rate was higher in DNR-loaded NP group in comparison with DNR group, and the relative expression of Caspase-3 protein was upregulated in DNR-loaded NP group compared with DNR group. Furthermore, DNR-loaded NPs obviously increased intracellular concentration of DNR in primary leukemia cells compared with DNR group, but there was no significant difference in primary cell apoptosis between the two groups. These findings suggest that the novel NP DDS can enhance the performance of conventional antitumor drugs and may be suitable for further application in the treatment of hematologic malignancies. Keywords: nanoparticles, transferrin, targeted drug delivery system, leukemia